Oral Methods of Urinary Alkalinization for High-dose Methotrexate Administration: Alternatives to Intravenous Sodium Bicarbonate During a Critical Drug Shortage. Issue 5 (July 2019) - Visage, Rachel; Kaiser, Nicole; Williams, Megan; Kim, Abby
Abstract : A nationwide shortage of intravenous (IV) sodium bicarbonate required institutions to explore alternative options for urinary alkalinization for high-dose methotrexate (HDMTX). Children's Hospital Colorado implemented a protocol utilizing oral alkalinizing agents as alternatives to intravenous sodium bicarbonate during the shortage. The purpose of this study was to determine the safety and efficacy of oral alkalinization strategies for HDMTX administration. This retrospective study was conducted at a pediatric institution and evaluated cycles of HDMTX administered with at least one dose of oral sodium bicarbonate tablets or sodium citrate-citric acid oral solution. The time to achieve urine pH of ≥7 was 3.48 hours from the start of alkalinization. A median dose of 66.4 mEq/m 2 /day of oral sodium bicarbonate was administered to maintain a urine pH of ≥7 until methotrexate was cleared. Gastrointestinal side effects occurred with 43% of HDMTX cycles and patients switched to IV sodium acetate in 25.5% of HDMTX cycles, primarily due to inadequate alkalinization or intolerance. During a shortage of IV sodium bicarbonate, oral alkalinization is an effective strategy for most patients to allow for administration of HDMTX.